2014
DOI: 10.1177/2167702614534210
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder Is Associated With Broad Impairments in Executive Function

Abstract: Obsessive-compulsive disorder (OCD) is a serious and often chronically disabling condition. The current dominant model of OCD focuses on abnormalities in prefrontal-striatal circuits that support executive function (EF). While there is growing evidence for EF impairments associated with OCD, results have been inconsistent, making the nature and magnitude of these impairments controversial. The current meta-analysis uses random-effects models to synthesize 110 previous studies that compared participants with OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
283
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(325 citation statements)
references
References 203 publications
23
283
5
Order By: Relevance
“…A more likely explanation of the slower RTs for OCD patients on the RIR pre-and post-test seems to be that the checking/RT dual task places higher demands on executive functioning (e.g., visuospatial working memory, general motor speed, and divided attention). Three recent meta-analyses showed that OCD is associated with broad impairments in cognitive functioning (i.e., verbal fluency, processing speed, attention, and executive function: inhibition, shifting, verbal and visuospatial working memory, and planning), although the magnitude of the effects is generally moderate (Abramovitch et al, 2013;Shin, Lee, Kim, & Kwon, 2014;Snyder, Kaiser, Warren, & Heller, 2014). We did not find evidence for general slower motor or processing speed in OCD patients.…”
Section: Discussioncontrasting
confidence: 66%
“…A more likely explanation of the slower RTs for OCD patients on the RIR pre-and post-test seems to be that the checking/RT dual task places higher demands on executive functioning (e.g., visuospatial working memory, general motor speed, and divided attention). Three recent meta-analyses showed that OCD is associated with broad impairments in cognitive functioning (i.e., verbal fluency, processing speed, attention, and executive function: inhibition, shifting, verbal and visuospatial working memory, and planning), although the magnitude of the effects is generally moderate (Abramovitch et al, 2013;Shin, Lee, Kim, & Kwon, 2014;Snyder, Kaiser, Warren, & Heller, 2014). We did not find evidence for general slower motor or processing speed in OCD patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Broadly speaking, anxious apprehension and anxious arousal have been associated with poorer behavioral performance and less efficiency (Eysenck et al, 2007;Silton et al, 2011;Warren et al, 2013) on tasks requiring attentional control. More specifically, anxious apprehension tends to correlate more with shifting impairments (Snyder et al, 2014) and anxious arousal more with dysfunctions in updating and inhibition (Warren, Heller, and Miller in prep). Additionally, these anxiety constructs correlate with distinct neural mechanisms that may disrupt specific executive functions e.g., for anxious apprehension, there is a negative correlation between neural activity in Broca's area, which putatively implements aspects of worry, and activity in DLPFC, which putatively implements top-down control of attention Spielberg et al, 2013).…”
Section: Executive Function Impairmentsmentioning
confidence: 96%
“…As evidence from clinical neuroscience and psychology has accumulated regarding the interactions among executive functions and dimensions of anxiety (e.g., Crocker et al, 2013;Levin et al, 2007;Snyder et al, 2014), it has become clear that deficits in executive function capacities can be predisposing risk factors, maintaining components, and/or negative consequences of anxiety disorders. Executive function is a broad term encompassing many cognitive processes, which in general coordinate behavior adaptively toward a goal (Banich, 2009).…”
Section: Executive Function Impairmentsmentioning
confidence: 99%
See 2 more Smart Citations